Preventive effect of different toothpastes on enamel erosion: AFM and SEM studies. Issue 4 (11th December 2013) - Lombardini, Marco; Ceci, Matteo; Colombo, Marco; Bianchi, Stefano; Poggio, Claudio
Summary The aim of the present in vitro study was the evaluation of new formulation toothpastes on preventing enamel erosion produced by a soft drink (Coca Cola), using atomic force microscopy (AFM) and scanning electron microscopy (SEM). Fifty enamel specimens were assigned to 10 groups of 5 specimens each. 1: intact enamel, 2: enamel + soft drink, 3: intact enamel + BioRepair Plus‐Sensitive Teeth, 4: enamel + soft drink + BioRepair Plus‐Sensitive Teeth, 5: intact enamel + BioRepair Plus‐Total Protection, 6: enamel + soft drink + BioRepair Plus‐Total Protection, group 7: intact enamel + Sensodyne Repair & Protect, 8: dentin + soft drink + Sensodyne Repair & Protect, 9: intact dentin + Colgate Sensitive Pro Relief, 10: dentin + soft drink + Colgate Sensitive Pro Relief. The surface of each specimen was imaged by AFM and SEM. The root mean‐square roughness (Rrms) was obtained from the AFM images and the differences in the averaged values among the groups were analyzed by ANOVA test. Comparing groups 4, 6, 8, 10 (soft drink + toothpastes) Colgate Sensitive Pro Relief promoted enamel remineralization, while BioRepair Plus‐Sensitive Teeth, Biorepair Plus‐Total Protection and Sensodyne Repair & Protect provided lower effectiveness in protecting enamel against erosion. Significance: the use of new formulation toothpastes can prevent enamel demineralization. SCANNING 36:401–410, 2014. © 2013 Wiley Periodicals, Inc.